(untitled) (Sinología hispánica. China Studies Review, 2022)
Spain and China share a long history of relations, which can be traced back to the Old Silk Road. Currently, the two countries are mutually important political, economic and trade partners. In recent decades, there has been a wave of Spanish language learning and of interest in topics related to the language. The work focuses on the understanding and translation of Chinese culturemes by Fray Juan Cobo (1547-1593) in the Spanish version of the Book Beng Sim Po Cam, using mainly the historical method of analysis, the hermeneutic theory and the textual research theory, with the aim of summarizing translation strategies of the evangelizer when carrying out his intercultural activities, in order to provide propitious experiences for future translational activities of such a nature.